2016
DOI: 10.1126/science.aaf1636
|View full text |Cite
|
Sign up to set email alerts
|

Throttling back the heart's molecular motor

Abstract: A small molecule inhibits mutated forms of myosin that cause cardiac hypertrophy [Also see Report by Green et al. ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…As described in section III, HCM is characterized by preserved or even increased contractility (hypercontractility). Recently, a small molecule, MYK-461, has been identified that reduces contractility by decreasing the ATPase activity of the cardiac MHC (142) [see also the accompanying edi-torial (464)]. These authors demonstrated that early, chronic administration of MYK-461 suppresses the development of ventricular hypertrophy, cardiomyocyte disarray, and myocardial fibrosis and attenuates hypertrophic and profibrotic gene expression in mice harboring heterozygous human MYH7 mutations.…”
Section: Small Molecule Myosin Activators and Inhibitorsmentioning
confidence: 99%
“…As described in section III, HCM is characterized by preserved or even increased contractility (hypercontractility). Recently, a small molecule, MYK-461, has been identified that reduces contractility by decreasing the ATPase activity of the cardiac MHC (142) [see also the accompanying edi-torial (464)]. These authors demonstrated that early, chronic administration of MYK-461 suppresses the development of ventricular hypertrophy, cardiomyocyte disarray, and myocardial fibrosis and attenuates hypertrophic and profibrotic gene expression in mice harboring heterozygous human MYH7 mutations.…”
Section: Small Molecule Myosin Activators and Inhibitorsmentioning
confidence: 99%
“…Such intervention could simplify treatment and become a generalized approach to control many contractile protein mutations that lead to HCM, or the use of myosin activators for dilated cardiomyopathy. (Adapted with permission from Warshaw, 7 Copyright Ó The American Association for the Advancement of Science.) The Journal of Thoracic and Cardiovascular Surgery c October 2016 identification of HCM patients before their clinical presentation.…”
Section: Myk-461 As a Cure For Hcm?mentioning
confidence: 99%
“…Thus, their motion is approximated by an overdamped stochastic process. Important examples include myosin [7], responsible for muscle contraction in cardiac and skeleton muscles, or kinesin/dynein for pulling cargos (e.g., organelles). They have the capability of producing force directly rather than via an intermediate energy, by converting chemical energy, e.g., adenosine triphosphate (ATP), to kinetic energy.…”
Section: Introductionmentioning
confidence: 99%